Design and Construction of a Combination Wave Generator - Marukatat, Nattapon; Tuethong, Piyapon; Yutthagowith, Peerawut (My University, 2019)
This paper presents design and construction of a combination wave generator with rating of 10 kV, 5kA. According to IEC 61000-4-5, the generator applies a lightning impulse voltage of 1.2/50-μs waveform in the condition of open circuit, and lightning impulse current of 8/20-μs waveform in the condition of short circuit. The generator can be used for testing surge suppression devices in the low-voltage system. The impulse generated by the generator can be controlled to impose on the DC and AC system low voltages. In the tests, the generator can apply the impulse on the system low voltage with selecting phase angle of 90o and 270o. From the test results, it can be confirmed that the generator can be used for the test efficiently.
Keywords: Combination wave generator; IEC 61000-4-5; Surge suppression device